EXPERT’S INSIGHTS The Western Balkans in the Mirror of the EU’s and Geopolitical Challenges - Meglena Plugtschieva (Bulgarian Journal of International Economics and Politics)
Western Balkans (WB) encompass six countries: Serbia, Bosnia and Herzegovina (BiH), Kosovo, Montenegro (MNE), Albania and North Macedonia (WB6). Given the importance of the Balkans for the European Union (EU), particularly in the light of recent geopolitical developments, the importance of the Ukraine war looms into importance and turns into watershed for WB-EU relations. The focus is therefore on the impact of the Ukraine war, but also that of the European Parliament’s (EP) elections on the WB-EU relationship. The analysis of these relations extends into a modest forecast for future developments outlining two possible scenarios depending on the development of the EU itself: a renewed and strong EU with a focus on integration or continued stagnation and growing nationalism with increase of centrifugal tendencies. The EU has the chance and the key opportunity to bring a positive change in the Western Balkans through strategic decisions and cooperation, thereby securing its own stability and prosperity. This is a shared European interest, and failure to act could turn the Balkans from a “white spot” on the political map into a “black hole.”